VARIASI GENETIK TANAMAN UJI KETURUNAN JATI ( Tectona grandis L.f ) UMUR 15 TAHUN DI PERUM PERHUTANI KPH CIAMIS DAN NGAWI - , Janser Aldomoro Saragi Rumahorbo, Prof. Dr. Ir. Mohammad Naâiem, M.Agr.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Recently, Teak Breeding still focused on wood growth improvement. Wood quality (specific gravity) has not become significant concern yet. In the future specific gravity will be intriguing on teak wood market. This research was conducted to look for the relation of specific gravity and growth on teak species trial at KPH Ngawi and Ciamis. Learning the relationship of specific gravity and growth will be implicated on genotype superior determination for height, diameter, specific gravity parameter. Height and diameter are obtained througt direct measuerement whereas specific gravity is estimated by pilodyn penetration and specific gravityâs regression model that tested first. Validation tested showed that pilodyn penetration and specific gravity model was valid and correlation value are -0.80 (Ngawi) and -0.73 (Ciamis). Analysis of varians explain family source of variation was significant. Genetic correlation are 0.98 height-dbh, 0.23 heightspesific gravity, 0.67 dbh-spesific gravity. heritability of family 0.13-0.32, genetic correlation 0.98 (height-dbh)